Epidemiological, Clinical, and Phylogenetic Characteristics of the First SARS-CoV-2 Transmission in a Nursing Home of Singapore: A Prospective Observational Investigation - Pang, Junxiong; Tan, Huei Nuo; Mak, Tze Minn; Octavia, Sophie; Maurer-Stroh, Sebastian; Sirota, Fernanda L.; Chan, Mark Peng Chew; Leong, Ian Yi Onn; Koh, Valerie T. J.; Ooi, Peng Lim; Vasoo, Shawn; Fisher, Dale; et al. (Frontiers in Medicine, 2022)
SARS-CoV-2 transmission has resulted in significant burden among nursing home facility globally. This prospective observational cohort study aims to define the potential sources of introduction and characteristics of SARS-CoV-2 transmission of the first nursing home facility in Singapore. An epidemiological serial point-prevalence survey of SARS-CoV-2 was conducted among 108 residents and 56 healthcare staff (HCS). 14 (13%) residents and two (3.6%) HCS were diagnosed with COVID-19, with case fatality rate of 28.6% (4/14) among the residents. The median age of the infected residents was 86.5 (IQR 78.5 to 88) and 85.7% were female. Five residents were symptomatic (35.7%) and the others were asymptomatic (64.3%). Higher proportion of residents who succumb to COVID-19 had hypertension than those who recovered. The SARS-CoV-2 whole-genome sequencing showed lineage B.6 which is rare globally but common regionally during early phase of pandemic. Household transmission is a potential source of introduction into nursing home, with at least six epidemiologically linked secondary cases. Male residents were less implicated due to the staff segregation plan by block. Among residents, a higher proportion of the non-survivors were asymptomatic and had hypertension compared to survivors.